Mindfulness levels among pre-service English language teachers: a comparative analysis of KIMS and MAAS scales - Servet Çelik; Şakire Erbay Çetinkaya; Yasemin Karsantık (Je-LKS: Journal of E-Learning and Knowledge Society)
Mindfulness practices have gained increasing attention in educational settings, including language classrooms, for their potential to benefit both learners and teachers. While research highlights the positive impact of mindfulness on language learners, its role in the professional development of language teachers remains an area of interest. This study explores mindfulness levels among pre-service English language teachers and examines the comparability of two widely used mindfulness assessments: the Kentucky Inventory of Mindfulness Skills (KIMS) and the Mindful Attention Awareness Scale (MAAS). A total of 148 pre-service English language teachers from a Turkish state university participated in this quantitative study. Data were collected through online self-reported questionnaires, with both KIMS and MAAS demonstrating acceptable reliability for this sample. Descriptive and inferential statistical analyses revealed that participants exhibited moderate mindfulness levels across both scales. While overall mindfulness levels did not significantly vary based on demographic factors, notable differences emerged in specific subcomponents of KIMS and MAAS concerning gender and class level. Additionally, significant relationships were found between mindful attention awareness and the ‘describe’ and ‘act with awareness’ dimensions of KIMS. These findings suggest that pre-service English language teachers generally demonstrate moderate mindfulness levels, regardless of demographic characteristics. Moreover, the comparability of KIMS and MAAS results indicates that both instruments can be effectively used to assess mindfulness in this population.